KEARIFAN SPIRITUAL DALAM PENDIDIKAN HUKUM LINGKUNGAN - Rahayu, Mella Ismelina Farma; Susanto, Anthon F.; Muliya, Liya Sukma (Faculty of Law, Universitas Pasundan, 2022)
This paper will describe and examine local wisdom values that are implemented in environmental law education in Indonesia. Environmental law education is now more oriented towards liberal environmental law education so that it ignores the values of local wisdom. Based on this, the problem that arises is how about local wisdom can be the basis for environmental law education by internalizing local wisdom in environmental law teaching materials. The study in this paper uses m The research approach method is normative juridical. Secondary data were gathered through literature searches and analyzed using qualitative legal analysis to reach conclusions using a deductive syllogism.From the results of the study, it was concluded that klocal wisdom is full of spiritual meaning and ethical values. This local wisdom rests on the philosophy of values, ethics, and ways of behaving and behaving that are traditionally institutionalized. This is an important basis for environmental law education, which is a guide for humans when dealing with their environment. Keyword : Wisdom, Values, Education, Environmental Law.